Lattice Parameter Changes for Spent UO2 Fuels With and Without Gd - Park, Yang-Soon; Kim, Jong-Goo; Seo, Hang-Seok; Ha, Yeong-Keong; Song, Kyuseok (Asian Journal of Chemistry, 2013)
The microstructural changes of spent nuclear fuels discharged from pressurized water reactors were investigated. The changes in the lattice parameters from the core to the rim of spent UO2 fuel specimens were measured using a radiation-shielded micro X-ray diffraction system (μ-XRD). For comparison, two different types of spent fuel pellets of 41 GWd/tU burnup were chosen as sample specimens, one containing PWR UO2 fuel and the other containing Gd-bearing UO2 fuel. The Gd-bearing UO2 fuel was chosen to investigate the effect of Gd on the lattice parameter of spent UO2 fuel. The lattice constant from the core to the rim of the specimen was larger for the spent UO2 fuel than for the fresh UO2 before irradiation. Although an overall lattice expansion was observed across the radius, the lattice contracts slightly near the outer surface of the fuel pellet. Based on the position where this lattice contraction was initiated, we predicted the thickness of the 'rim' region as 100 μm. For spent Gd-bearing UO2 fuel, the lattice across the radius of specimen is larger than that of fresh Gd-bearing UO2 fuel but smaller than that of fresh UO2 due to Gd dissolution in the UO2 lattice.